2020
DOI: 10.1111/rec.12983
|View full text |Cite
|
Sign up to set email alerts
|

Chronosequence of former kaolinite open cast mines suggests active intervention is required for the restoration of Atlantic heathland

Abstract: Atlantic lowland heath (ALH) is a priority conservation habitat in Western Europe, but restoration efforts have met with mixed success due to the complexity associated with replicating establishment conditions. By virtue of their impoverished, often acidic soils and geographic location in areas naturally occupied by ALH communities, former kaolinite mine sites may offer an excellent opportunity for heathland restoration. Using a chronosequence of former open cast kaolinite mines in South West England (0, 2, 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…(3) “Metals”: Cations were added at the following amounts per plot; sodium 123 g (13.50 mg/kg), calcium 111 g (12.5 mg/kg), potassium 324 g (35.40 mg/kg), and magnesium 449 g (49.03 mg/kg). These amounts were based on Lane et al (2019) to increase observed levels in stored overburden to heathland soil concentrations reported by Clarke (1997). Applied in pellet form (Thompson and Morgan, Suffolk, U.K.), the cations were mixed and broadcast by hand to ensure an even spread.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) “Metals”: Cations were added at the following amounts per plot; sodium 123 g (13.50 mg/kg), calcium 111 g (12.5 mg/kg), potassium 324 g (35.40 mg/kg), and magnesium 449 g (49.03 mg/kg). These amounts were based on Lane et al (2019) to increase observed levels in stored overburden to heathland soil concentrations reported by Clarke (1997). Applied in pellet form (Thompson and Morgan, Suffolk, U.K.), the cations were mixed and broadcast by hand to ensure an even spread.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the ability of many heathland species to cope with a stressful edaphic environment, the removal and storage of overburden, later used for mine rehabilitation, often reduces nutrient concentrations to levels well below those naturally found in heathland soils and insufficient for plant establishment and growth (Coppin & Bradshaw 1982; Clarke 1993, 1997; Lane et al 2019). Overburden storage can also raise pH to levels unsuitable for heathland establishment, and encourage instead recruitment of competitive grass species that limit ericaceous plant establishment (Marrs et al 1998; Green et al 2015; Lane et al 2019). Moreover, reinstatement of a carbon and nutrient‐limited, highly porous mineral overburden inevitably limits heathland establishment (Diaz et al 2006; Smith & Read 2010; Machado et al 2013; Bateman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Lane et al () and collaborators found that mesotrophic grasses dominated former kaolinite mining sites, instead of typical lowland heath species. Such differences in vegetation composition were attributed to soil characteristics, which revealed lower acidity levels and organic content.…”
Section: The Challenges Of Restoring Quarriesmentioning
confidence: 99%
“…Some studies have shown that only the presence of both above-(vegetation) and belowground (microbiota and fauna) heathland species leads to a fast assembly toward the target ecosystem [81,83]. Therefore, in terms of assessing the efficacy of application of elemental sulphur to acidify pasture, sole reliance on chemical indicators to quantify the success of a restoration may lead to misleading conclusions.…”
Section: Belowground Response To Changes In Soil Chemical Propertiesmentioning
confidence: 99%